Introduction: Transcending the State—A Transnational Account of Turkish Foreign Policy - Kuru, Deniz; PAPUÇÇULAR, HAZAL (Palgrave Macmillan, 2020)
The introduction provides a summary of all the chapters, and explains why the editors chose to focus on the transnational dimensions of Turkish foreign policy. It aims to fulfill a two-fold task: bringing in more from transnational approaches and transnationalist studies into foreign policy research and doing this in the specific Turkish context that is mostly framed in state-centric terms. By elaborating the volume’s main insights and highlighting the contributors’ theoretical frameworks and empirical/case studies, it simultaneously emphasizes the multiple ways in which the separate thematic sections and the related chapters therein complement each other. It shows how this approach differs from the mainstream literature on Turkish foreign policy, and goes beyond a mere focus on contemporary political developments, as it also engages with significant examples of transnational dynamics in Turkish foreign policy in different periods.
Keywords: Turkish foreign policy